Reconstructing Islamic Family Law through a Monistic Paradigm: An Interdisciplinary Perspective - Muhammad Nabil; Ihsan; Nur Said (Hikmatuna : Journal for Integrative Islamic Studies, 2026)
A methodological dichotomy between normative jurisprudential approaches and empirical socio-legal perspectives has long fragmented Islamic family law, resulting in inconsistent responses to contemporary challenges. This article addresses this gap by operationalising a monistic paradigm as a concrete epistemological framework for legal reconstruction. Rather than an abstract philosophical concept, monism is defined here as a structured synthesis of textual sources, empirical socio-legal realities, and policy-judicial applications, all anchored in maqāṣid al-sharīʿah. Methodologically, the study employs a qualitative-comparative design with a normative-empirical orientation. Data comprises primary legal texts, contemporary court decisions, and interdisciplinary socio-legal literature. The framework’s applicability is demonstrated through targeted case studies, digital divorce validation and women’s inheritance rights, which serve as analytical lenses to show how monistic reasoning reconciles classical norms with modern shifts without compromising normative integrity. The findings indicate that monism successfully bridges theoretical fragmentation into an actionable reform methodology. Practically, it equips policymakers and judges with a coherent, maqāṣid-driven tool for drafting adaptive legislation, thereby offering a replicable pathway for achieving religiously grounded yet socially responsive legal harmonisation in contemporary Muslim societies.